On the operating parameters for hydrogen-rich syngas production in a plasma co-gasification process of municipal solid wastes and polypropylene using a constrained model in Aspen plus. (April 2023) - Okati, Armin; Khani, Mohammad Reza; Shokri, Babak; Monteiro, Eliseu; Rouboa, Abel
Abstract: Polypropylene and municipal solid wastes (MSW) are produced in large quantities presenting a serious environmental problem. Plasma gasification is one of the most environmentally friendly processes for the elimination of plastic wastes and MSW due to the high temperatures that guarantee that toxic compounds are decomposed. The feasibility of the plasma co-gasification of MSW and polypropylene wastes was investigated through a constrained model developed in Aspen Plus®. A parametric study was performed to investigate the effect of important parameters such as temperature, equivalence ratio, steam-to-waste ratio, and different ratios of polypropylene in the feedstock on the quality of syngas and hydrogen production. The good agreement of the model results with literature results ensures the robustness of the simulation's performance. The results suggest that the highest molar fractions of hydrogen are obtained with higher proportions of polyethylene in the waste mixture. Low air-to-waste ratios and low equivalence ratios are favorable to hydrogen generation. The amount of steam injected into the co-gasification system and temperature variation have a minor effect on hydrogen production. These findings could help launch plasma co-gasification industrial projects as a new waste-to-energy management method. Highlights: Optimum parameters of plasma gasification of MSW and polypropylene are studied. High amount of polypropylene is suitable for H2 production. Higher amounts of H2 are obtained for low equivalence ratios. Steam-to-waste ratio and temperature have a minor effect on H2 production. Low temperatures should be used in favor of process efficiency.